Antimicrobial Effects of Vapor Phase Thymol, Modified Atmosphere, and Their Combination against Salmonella spp. on Raw Shrimp. Issue 5 (9th April 2013) - Zhou, Siyuan; Sheen, Shiowshuh; Pang, Yu‐Hsin; Liu, LinShu; Yam, Kit L.
Abstract Salmonella contamination on raw shrimp is a big food safety concern in the United States currently. This research evaluated the inhibition effects of vapor phase thymol, modified atmosphere (MA), and their combination against Salmonella spp. on raw shrimp. Growth profiles of a Salmonella spp. cocktail (6 strains), inoculated onto the surface of raw shrimp, treated with vapor phase thymol at 3 levels (0, 0.8, and 1.6 mg/L), or MA (59.5% CO2 + 39.5% N2 + 1% O2), both alone and in combination, at 3 temperatures (8, 12, and 16 ºC), were determined. Lag time and maximum growth rate of Salmonella spp. under each treatment were obtained using Baranyi and Roberts models. Results indicated that both vapor phase thymol and MA treatments alone inhibited the growth potential of Salmonella spp. effectively, extending the lag time by 10% to 100% and reducing the maximum growth rate by 14% to 71% compared with controlled samples at experimental temperatures (8, 12, and 16 ºC). Combination treatments of vapor phase thymol and MA exhibited greater inhibition effectiveness than each individual treatment and a synergistic antimicrobial effectiveness could be observed on the lag time extension. To the maximum, at 12 ºC, lag time of Salmonella spp. was extended 59.6% more by the combination treatment of 0.8 mg/L thymol + MA (36.97 h) than those effects combined from 0.8 mg/L thymol treatment and MA treatment alone (23.16 h in total). This combination strategy could be potentially utilized for Salmonella inhibition during the long distance and temperature‐abused raw shrimp import process. Practical Application The vapor phase thymol + MA combination strategy could be potentially applied in temperature‐abused and long‐distance raw shrimp import process to retard the Salmonella spp. growth, therefore reducing its import rejection rate as well as enhancing its food safety level to the consumers' concerns.